2017
DOI: 10.3390/children4090078
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Parent Peer Nutrition Educators Sharing Child Feeding and Nutrition Information

Abstract: The aim of this study was to describe the experiences of parents as peer educators disseminating nutrition and child feeding information. Parents of infants aged from birth to three years were trained as peer educators in a face-to-face workshop, and then shared evidence-based child feeding and nutrition information via Facebook, email, and printed resources for six months to peers, family, and social media contacts. Semi-structured telephone or group interviews were conducted after a six-month online and face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 31 publications
0
23
0
1
Order By: Relevance
“…The PICNIC model has been informed by The Food For Kids Mid North Coast (FFKMNC) pilot study [21]. The FFKMNC study reported the experiences of new parents (n = 28) in the role of nutrition peer educators and demonstrated peer to peer education is acceptable with new parents to share evidence based infant nutrition and child feeding messages [21].…”
Section: Intervention Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The PICNIC model has been informed by The Food For Kids Mid North Coast (FFKMNC) pilot study [21]. The FFKMNC study reported the experiences of new parents (n = 28) in the role of nutrition peer educators and demonstrated peer to peer education is acceptable with new parents to share evidence based infant nutrition and child feeding messages [21].…”
Section: Intervention Developmentmentioning
confidence: 99%
“…The PICNIC model has been informed by The Food For Kids Mid North Coast (FFKMNC) pilot study [21]. The FFKMNC study reported the experiences of new parents (n = 28) in the role of nutrition peer educators and demonstrated peer to peer education is acceptable with new parents to share evidence based infant nutrition and child feeding messages [21]. Recommendations from the FFKMNC that informed the PICNIC model included recruitment earlier in the parenting cycle (before child aged six months), focusing information on feeding practices which positively influence feeding behaviour, improved access to online content via social media and the creation of a project specific website developed by an established Health Promotion Team within a Health Service framework [21].…”
Section: Intervention Developmentmentioning
confidence: 99%
See 3 more Smart Citations